Karakteristik Lotion Anti Nyamuk Kombinasi Ekstrak Sabut Kelapa (Cocos nucifera) dan Bunga Kamboja (Plumeria sp.) - Sriwulan Sriwulan; Fabella Eka Fulyani; Siti Aisah; Ummu Rosyidah; Isaiah Imam Murtadho; Isaiah Imam Mawardi (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2023)
Mosquitoes are vectors of several diseases, one of which is Dengue Hemorrhagic Fever. Therefore, it is necessary to take steps to prevent the spread of the disease. One of them by using anti-mosquito lotion. However, some of commercial lotions are made of chemicals that have side effects on health. Therefore, coconut coir (Cocos nucifera L.) and frangipani flower anti-mosquito lotion was developed. Coconut coir contains tannins which repel insects and have a therapeutic effect. Frangipani flowers contain geraniol which can repel insects. The purpose of this study was to determine the characteristic of coconut coir extract (Cocos nucifera L.) with a combination of frangipani flower extract (Plumeria sp.) as a lotion preparation. This research is an experimental study with 7 treatments of lotion formulation.. The data in this study include organoleptic tests, homogeneity tests, pH, and spreadibility of the lotion. The conclusion of this study showed that a lotion formula P3 with a ratio of 1:2 (coconut coir extract:frangipani flower extract) was the best formulation with the characteristics of a fine solid texture, brownish yellow color, frangipani fragrant, homogeneous, have pH 6, and the diameter of spread is 7,5cm.